Changes in Umbilical and Cerebral Blood Flow in Pregnancies Diagnosed with Clinical Chorioamnionitis. Is Chorioamnionitis Predictable? - Okmen Ozkan, Berfin; Ekmekci, Emre (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: To evaluate the predictability of clinical chorioamnionitis by Doppler changes in fetal middle cerebral and umbilical arteries, at hospitalized patients due to preterm premature rupture of membranes. Study Design: Patients who were admitted and hospitalized due to preterm premature rupture of membranes between 24 weeks and 33 weeks and 6 days pregnancies are included in the study. Demographic data of patients, gestational age at referring to hospitalization, fetal presentation at admission, delivery time, delivery indications and total follow-up time until delivery of each case were recorded. Results: A total of 108 patients were evaluated retrospectively. The rate of clinical chorioamnionitis was 5.55% (6/108). There was no significant difference between pregnancies terminated with the diagnosis of clinical chorioamnionitis and pregnancies terminated with other indications in terms of the maximum systolic velocity at middle cerebral artery and umbilical artery pulsatility indices. Conclusion: Clinical chorioamnionitis is a serious complication and is more common in patients being followed up after preterm premature rupture of membranes. Although it is crucial to be predicted due to neonatal worse prognosis, it cannot be predicted by middle cerebral and umbilical artery Doppler evaluation.